2017
DOI: 10.1002/biot.201700250
|View full text |Cite
|
Sign up to set email alerts
|

Cell Separation in Aqueous Two‐Phase Systems − Influence of Polymer Molecular Weight and Tie‐Line Length on the Resolution of Five Model Cell Lines

Abstract: The availability of clinical-scale downstream processing strategies for cell-based products presents a critical juncture between basic research and clinical development. Aqueous two-phase systems (ATPS) facilitate the label-free, scalable, and cost-effective separation of cells, and are a versatile tool for downstream processing of cell-based therapeutics. Here, we report the application of a previously developed robotic screening platform, here extended to enable a multiplexed high-throughput cell partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the past, the integration of robotic systems for downstream process development led to significant increases in the throughput of several standard operation procedures. For example, cell lysis has been optimized for improved release of intracellular products, the screening of chromatographic material and binding/elution conditions was facilitated, and the identification of optimal compositions of aqueous two‐phase systems or precipitation conditions has become experimentally feasible. So far only a few but highly interesting studies have been reported that combine high‐throughput upstream and downstream bioprocess development .…”
Section: Microbioreactor (Mbr) Systemsmentioning
confidence: 99%
“…In the past, the integration of robotic systems for downstream process development led to significant increases in the throughput of several standard operation procedures. For example, cell lysis has been optimized for improved release of intracellular products, the screening of chromatographic material and binding/elution conditions was facilitated, and the identification of optimal compositions of aqueous two‐phase systems or precipitation conditions has become experimentally feasible. So far only a few but highly interesting studies have been reported that combine high‐throughput upstream and downstream bioprocess development .…”
Section: Microbioreactor (Mbr) Systemsmentioning
confidence: 99%
“…They are formed when two hydrophilic compounds such as polymers, salts or ionic liquids are combined above critical concentrations, resulting in the formation of two immiscible phases . The resulting phases have different concentrations of both compounds and thus different electrochemical and hydrophobic characteristics, allowing the partition of biomolecules according to their intrinsic properties . However, such systems lack specificity when the differences between the component of interest and the contaminants (red blood cells, non‐viable cells, cell debris and other mononuclear cells) are small.…”
Section: Introductionmentioning
confidence: 99%